Designing for additive manufacturing - Pontes, A. J. (2021)
Additive manufacturing (AM) technologies have emerged as an industrial response to improve, simplify, and accelerate the stages of product development. The available layer-by-layer techniques and building materials, combined with, e.g., geometric freedom, processing speed, tool independency, ability to generate multimaterial products in a single-step process, and the possibility to embed components for enhanced functionality, provide new capabilities that expand the applications possibilities from prototypes and tools, up to final functional parts personalized with unique and distinctive characteristics. AM technologies are applied in biomedical (medical implants, prosthetics), architectural (modeling, construction), rapid tooling (jig fixtures), hybrid molds (molding inserts, conformal cooling), aerospace (lightweight structures), aviation and automotive (lightweight components, heat sinks). These potentialities and versatility of AM are impacting the industrial world toward a new era. In this chapter, the main AM technologies are described, and basic design rules and key benefits are introduced in the context of process optimization and product development.